Characteristics of albumin and globulin from coconut meat and their role in emulsion stability without and with proteolysis. (August 2017) - Patil, Umesh; Benjakul, Soottawat
Abstract: Albumin and globulin were fractionated from defatted coconut meat. Characteristics and emulsifying properties of these protein fractions were comparatively studied. Both fractions had protein with MW of 55 kDa as predominant and glutamine/glutamic acid were the major amino acids. However, differences in the protein pattern and amino acid composition were observed between two fractions. Higher average hydrophobicity was found in globulin fraction, compared with albumin. Additionally, globulin fraction was more hydrolyzed by Alcalase, in comparison with albumin. Coconut milk oil-in-water model emulsion was prepared using albumin and globulin protein fractions and stability of these emulsions was evaluated. Oil droplets with larger size caused by coalescence along with higher polydispersity were observed in albumin stabilized emulsion after 24 h of storage time. Conversely, globulin stabilized emulsion showed smaller oil droplet with low coalescence index and flocculation factor. Thus, emulsion stabilized by globulin fraction was more stable than that containing albumin fraction. However, the higher oil recovery was found in the globulin stabilized emulsion when treated with 1% Alcalase for 90 min, compared with albumin counterpart. This was caused by the higher susceptibility towards hydrolysis of globulin fraction. Therefore, globulin fraction mainly determined coconut milk stability and must be hydrolyzed by protease to release oil for virgin coconut oil production. Graphical abstract: Highlights: Albumin and globulin were the dominant proteins in defatted coconut meat. Globulin had higher average hydrophobicity, compared with albumin. Globulin stabilized emulsion was more stable than albumin stabilized counterpart. Globulin was more susceptible toward hydrolysis by Alcalase than albumin. Oil could be released from emulsion via Alcalase hydrolysis.